Alleviation of hyperglycemia and hyperlipidemia by Phyllanthus virgatus forst extract and its partially purified fraction in streptozotocin induced diabetic rats - Hashim, Arshya (EXCLI J, 2014)
Since, we previously demonstrated that sequentially extracted methanolic fraction showed marked antioxidant and antidiabetic property in vitro, the present study was design to evaluate the beneficial effects of Phyllanthus virgatus methanolic extract and its partially purified fraction on hyperglycemia and hyperlipidemia in streptozotocin (STZ) induced diabetic rats. The plant extract was subjected to repeated thin layer chromatographic fractionation followed by GC-MS analysis of active fraction. TLC data illustrated the presence of six prominent bands and the prelimnary screening of these bands against α-amylase inhibitory activity showed that the band with R(f) value 0.514 has marked inhibitory property (IC(50), 48 µg/ml). The diabetic rats were treated for four weeks with methanolic extract of P. virgatus (50 and 10 mg/rat/day), partially isolated active fraction (0.5 and 0.1 mg/rat/day) and glibenclamide (0.1 mg/rat/day). The level of fasting blood glucose (FBG), hemoglobin, glycated hemoglobin (HbA1c) and insulin were significantly alleviated in plant extract and partially purified fraction treated group after 28 days of administration. Moreover, total cholesterol (TC), triglycerides (TG), low density lipoprotein-cholesterol (LDL-C), very low density lipoprotein-cholesterol (VLDL-C) and high density lipoprotein cholesterol (HDL-C) were also markedly ameliorated in the entire treatment group, with a maximum restoration observed in group treated with partially purified fraction (0.5 mg/rat/day). The results demonstrate a strong antidiabetic and hypolipidemic impact of plant extract and its partially purified fraction coupled with their potent antioxidative property, which can provide additional benefits in the inhibition of oxidative stress and hence in the prevention and treatment of diabetes as well as diabetes linked hyperlipidemia.